Tracking the space-time evolution of ocean acidification extremes in the California Current System and Northeast Pacific - Desmet, Flora; Gruber, Nicolas; id_orcid:0 000-0002-2085-2310; Köhn, Eike E.; Münnich, Matthias; id_orcid:0 000-0003-3292-2934; Vogt, Meike (American Geophysical Union, 2022)
Ocean acidification is punctuated by episodic extremes of low pH and saturation state with regard to aragonite (omega(A)). Here, we use a hindcast simulation from 1984 to 2019 with a high-resolution regional ocean model (ROMS-BEC) to identify and track ocean acidification extremes (OAX) in the northeast Pacific and the California current system (CCS). In the first step, we identify all grid-cells whose pH and omega(A) are simultaneously below their first percentile over the analysis period (1984-2019). In the second step, we aggregate all neighboring cells with extreme conditions into three-dimensional time evolving events, permitting us to track them in a Lagrangian manner over their lifetime. We detect more than 22 thousand events that occur at least once in the upper 100 m during their lifetime, with broad distributions in terms of size, duration, volume, and intensity, and with 26% of them harboring corrosive conditions (omega(A) < 1). By clustering the OAXs, we find three types of extremes in the CCS. Near the coast, intense, shallow, and short-lasting OAXs dominate, caused by strong upwelling. A second type consists of large and long-lasting OAX events that are associated with westward propagating cyclonic eddies. They account for only 3% of all extremes, but are the most severe events. The third type is small extremes at depth arising from pycnocline heave. OAXs potentially have deleterious effects on marine life. Marine calcifiers, such as pteropods, might be especially impacted by the long-lasting events with corrosive conditions. ISSN:0148-0227 ISSN:2169-9275